OUTDOOR GAMES IN THE EDUCATIONAL AND TRAINING PROCESS FOR YOUNG WRESTLERS OF THE GRECO-ROMAN STYLE - Zufarov Temur Umarovich (Proximus Journal Publishing, 2025)
The paper shows and substantiates the feasibility of using the concept of training in the form of outdoor games based on experimental data, theoretical generalizations and methodological provisions. The implementation of outdoor games in the educational and training process of young wrestlers of the GrecoRoman style according to the identified criteria and aspects will ensure an increase in the level of fundamental training and the quality of the training and education process
Keywords: outdoor games; Greco-Roman wrestling; young wrestlers